Postoperative Complications After Operative Treatment of Open Versus Closed Distal Radius Fractures: A Propensity Score Matched Analysis - R. Cole Schmidt, MD; Conor N. O’Neill, MD; Zakkary J. Walterscheid, MD; James R. Satalich, MD; Jonathan Isaacs, MD (Journal of Hand Surgery Global Online)
Purpose: The primary objective was to use a large sample size to compare 30-day infection rates and other perioperative outcomes between operatively treated open and closed distal radius fractures. Methods: Patients in the American College of Surgeons National Surgical Quality Improvement Program database who underwent open reduction and internal fixation of a distal radius fracture between 2008 and 2018 were identified using Current Procedural Terminology codes and stratified into open (OF) and closed fractures (CF). A 10:1 (CF:OF) nearest neighbor propensity score matching was used to address demographic differences. Infection rate and other outcomes were compared between groups. Results: A total 17,536 CF and 401 OF were treated by open reduction and internal fixation. After matching, baseline demographics were not statistically different (P > .05). There was a statistically significant increase in deep surgical site infections between OF and CF (0.2% vs 0.02%, P < .05). The OF cohort had a higher rate of significant adverse events (7.2% vs 1.6%, P < .05), return to the operating room (3.5% vs 0.9%, P < .05), mean length of stay (1.8 vs 0.7 days, P < .05), and operative time (90.8 vs 73.7 minutes, P < .05), but no difference in time from admission to the operating room (0.4 vs 0.3 days). Conclusions: There was a statistically but probably not clinically impactful increase in 30-day deep surgical site infections in OF compared to CF. Patients with OF had significantly longer operative times and length of stay, and more often returned to the OR. This suggests that many OF patients do not carry a clinically increased short-term risk of infection when compared to CF patients. Type of study/level of evidence: Prognostic, Level III.